Ultra large pitch and depth structures metrology using spectral reflectometry in combination with RCWA based model and TLM Algorithm : AM: Advanced Metrology - Vito, Annalisa Del; Osherov, Ilya; Urbanowicz, Adam Michal; Katz, Yinon; Barkan, Kobi; Turovets, Igor; Haupt, Ronny (ASMC proceedings, 2020)
The mainstream of dimensional metrology development is focused towards continuous shrinking of the devices (Moore scaling). Current cutting-edge technologies are in few nanometer range (3-7nm). There is also a growing demand to characterize structures with large dimensions in microns range (pitch, CD or depth). New technology megatrends such as internet of things (IOT) additionally require More than Moore scaling and heterogeneous integration [1-3]. Due to recent developments ultra large pitch scatterometry applications growth is observed in high power, sensors and packaging areas. Here we present novel approach that is focused on ultra large pitch scatterometry and its challenges. We demonstrate how to extend usage of conventional scatterometry for micro size devices.